Genetic Variants, Prediagnostic Circulating Levels of Insulin-like Growth Factors, Insulin, and Glucose and the Risk of Colorectal Cancer: The Multiethnic Cohort Study - Ollberding, Nicholas J. (Cancer Epidemiol Biomarkers Prev, 2012)
BACKGROUND: Increased exposure of colonic and rectal epithelial cells to the promitotic and antiapoptotic effects of insulin and insulin-like growth factors (IGF) is hypothesized to increase colorectal cancer risk. METHODS: In a case–control study nested within the Multiethnic Cohort, we attempted to replicate associations for five genetic variants associated with IGF system biomarkers, insulin, or glucose and to examine their association with the risk of colorectal cancer. In a subset of participants, the association between circulating biomarkers and colorectal cancer risk was examined. Unconditional logistic regression was used to calculate ORs and 95% confidence intervals (CI) for genetic variants (1,954 cases/2,587 controls) and serum biomarkers (258 cases/1,701 controls). RESULTS: Associations with circulating biomarkers were replicated in the Multiethnic Cohort for IGF1 rs35767 and for IGFBP3 rs2854744, rs2854746, and rs3110697 (P < 0.05). Homozygous carriers of the glucokinase regulator (GCKR) rs780094 variant T-allele were at a decreased risk of colorectal cancer (OR, 0.77; 95% CI, 0.64–0.92). In risk factor–adjusted models, participants with the highest prediagnostic IGF-II levels were at an increased risk [OR (T1 vs. T3), 1.58; 95% CI, 1.09–2.28; P(trend) = 0.011] and participants with the highest prediagnostic IGF-binding protein (IGFBP)-3 levels were at a decreased risk of colorectal cancer (OR, 0.53; 95% CI, 0.34–0.83; P(trend) = 0.003). CONCLUSION: These data provide further support for a role of prediagnostic IGF and insulin levels in the etiology of colorectal cancer. IMPACT: Future studies attempting to replicate the association between the GCKR rs780094 variant and the risk of colorectal cancer are warranted.